Prescription Adaptation Services: A Win for Patients and Providers - Alex J. Adams (University of Minnesota Libraries Publishing, 2020)
"Prescription adaptation services" (PAS) refers to the ability of pharmacists "to adapt an existing prescription when, in their professional judgment, the action is intended to optimize the therapeutic outcome of treatment." If structured appropriately, PAS can provide a benefit in enhancing the timeliness of patient care, while reducing the administrative burden on both physicians and pharmacists. Moreover, it leverages the strengths of both health professions, specifically the medication expertise of pharmacists. Unfortunately, in most states it will require a change in regulations in order to enable PAS.